An automated soil surface profile machine and a method of measuring soil surface profile - Yahya, Azmi; Weng, Beng Sui (2009)
The present invention provides systems and methods for an automated,mobile-type 2-axis laser soil surface profile digitizer for measuring and digitizing soil surface roughness parameters. The sensing device utilized the industrial-type laser displacement sensor, which is equipped with build-in emitter, receiver, and signal conditioning circuitry. Transportation, uplifting and releasing mechanism of the measurement apparatus during field operation is provided by a special design hydraulically-powered open-base trailer, and pulled by an agricultural tractor. Programmable Logic Controller (PLC) unit and its external electronic circuits and sensing devices perform the intelligent motion control for the digitizer. Two stepper motors drive the sensor in 2-axis of digitizing direction. The simplified method of the user programming platform. The system is capable to digitize a maximum area of 1.05m x 1.8m with an adjustable digitizing speed, digitizing interval and digitizing area to suit with the required operation time and output resolution. The field setup operation is simplified by the use of four adjustable measurement apparatus supporters.